History and Context in Comparative Public Policy. - Ashford, Douglas E. (Pittsburgh : University of Pittsburgh Press, 1992)
Through a series of essays, this volume argues that every political system is based on a substratum of shared intentions, meanings, and rules of conduct embedded in a culture.
8. Functionalism and Policy Studies -- 9. Welfare Ideologies and State Policies: British Oppositions -- 10. Policy Constitution Through Discourse: Discourse Transformations and the Modern State in Central Europe -- 11. Political Science and Policy Studies -- Part III -- In Search of Agency -- 12. Parties, Politics and Democratic Choice -- 13. Public Policy and Public Bureaucracy -- 14. Ordaining Powers: Rediscovering the State Through Policy Studies -- 15. Conclusion: The Policy Connection: Subject or Object? -- Notes on Contributors
Description based upon print version of record.
JSTOR
Keywords: Comparative government; Welfare state; Policy sciences; État providence; Sciences de la politique; 88.70 comparative study of public administration; POLITICAL SCIENCE / General; Welfare state; Policy sciences; Comparative government; Kongress; Aufsatzsammlung; Vergleichende politische Wissenschaft; Politische Wissenschaft; Beleidsanalyse; Vergelijkende bestuurskunde; Congresses (form)